'Indigenous Plots in Twenty-First Century Latin American Cinema' - Milton Fernando González Rodríguez (European Review of Latin American and Caribbean Studies)
Indigenous Plots in Twenty-First Century Latin American Cinema, by Maria Chiara D’Argenio, Springer, 2022